The impact of the COVID-19 pandemic on physical activity, life satisfaction, anxiety, stress perception and coping strategies in student-athletes: A comparison between Belarus and Poland–countries with a different approach of anti-pandemic measures - Shpakou, Andrei; Sokołowska, Dorota; Krajewska-Kułak, Elżbieta; Cybulski, Mateusz; Kowalewska, Beata; Korpak, Filip; Surkov, Sergei; Owoc, Jakub; Krakowiak, Jan; Kowalczuk, Krystyna (Frontiers in Public Health, 2022)
Background More than two years of the COVID-19 pandemic has changed lives of people around the world and had a profound impact on the field of sports. This has resulted in decreased physical activity (PA) and changes in mental health. The goal was to assess self-reported physical activity, life satisfaction, perceived stress, choice of coping strategies and their correlations among student athletes from two neighboring countries facing different anti-pandemic strategies. Methods Cross-sectional surveys using standardized questionnaires: International Physical Activity Questionnaire—Short Form (IPAQ-SF), Satisfaction With Life Scale (SWLS), State-Trait Anxiety Inventory (STAI), Perceived Stress Scale (PSS-10), and Coping Orientation to Problems Experienced (Mini-COPE) to compare 600 students from Physical Education and Sports departments of universities in Belarus (n = 333), where restrictions were found to be less stringent than in neighboring Poland (n = 267). Results Minor differences in physical activities between both countries indicate that student athletes have adapted fairly quickly and found ways to keep their PA at a fairly high level. Nevertheless, higher PA was reported in the group of student athletes from Belarus. PA levels correlated with life satisfaction, anxiety and stress levels. Female students from Poland reported lower satisfaction with their lives. Their perception of stress was twice as high as that of their Belarusian counterparts. The most common coping strategy in both groups was active coping. Polish respondents less frequently used strategies of avoiding problems and seeking outside support. Conclusion The level of physical activity and well-being of student athletes are associated with increased mental health and coping with stress. They also contribute to prevention of affective disorders during the COVID-19 pandemic. Moreover, it is dependent on the country's anti-pandemic policies.